1984
DOI: 10.1111/j.1440-1681.1984.tb00234.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic Effects of a Single Low Dose of Prazosin in Patients With Chronic Congestive Cardiac Failure Correlations With Pharmacokinetics

Abstract: The haemodynamic effects and pharmacokinetics of a single orally administered dose of 0.5 mg of prazosin have been compared in six patients with stable severe congestive cardiac failure. Administration of prazosin induced significant decreases in mean pulmonary capillary wedge pressure (from 27.5, s.e.m. = 4.5 to 19.4, s.e.m. = 5.1 mmHg; P less than 0.001), mean arterial blood pressure (from 94.5, s.e.m. = 6.0 to 85.4, s.e.m. = 5.0 mmHg; P less than 0.01), and systemic vascular resistance (from 1690, s.e.m. = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…12 Short-term studies suggested that alpha blockers might have beneficial haemodynamic effects in patients with heart failure. [13][14][15] These findings however were mainly confined to patients receiving prazosin and not doxazosin.…”
mentioning
confidence: 99%
“…12 Short-term studies suggested that alpha blockers might have beneficial haemodynamic effects in patients with heart failure. [13][14][15] These findings however were mainly confined to patients receiving prazosin and not doxazosin.…”
mentioning
confidence: 99%